Integrative Model of Religious Habituation in Building Students Religious Character - Nursobah, Asep; Arjuna, Arjuna; Ulhaq, Muhammad Miftah; Ariska, Mutiara (Sekolah Tinggi Agam Islam Sumatera Medan, 2025)
This study addresses the challenges of Islamic vocational education in developing students’ religious character alongside professional skills. At SMK Al-Azhar Batam, religious habituation strategically instills values such as discipline, honesty, trustworthiness, courage, self-confidence, love for Islam, and noble character within vocational activities. The research aims to understand the role of religious habituation in character development, examine values reflected in vocational practice, describe the internalization process, and identify supporting and inhibiting factors. Using a qualitative case study with interviews, observations, and documentation, the study finds that internalization occurs through six continuous stages: value planting, habituation, vocational integration, teacher modeling, internalization, and cultural embedding. Success depends on school commitment, teacher role models, program regularity, and facilities, while obstacles include students’ motivation, diverse backgrounds, external influences, and a demanding curriculum. The study implies the need for family-based, integrative strategies and alignment of religious values with vocational practice to sustain character internalization.